Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-22T16:02:36+01:00
Ex 2:
on pose X=sin(x) et Y=cos(x)
donc
{2X-4Y=√3+2
{X+√3Y=0
donc
{2X-4Y=√3+2
{2X+2√3Y=0
donc
Y=(2+√3)/(-4-2√3)
Y=-1/2
sin(x)=-1/2
aussi
X=-√3*Y
X=√3/2
cos(x)=√3/2
donc x=11π/6 rad

Ex 3
S=sin(x+π/2)+sin(x+π)+sin(x+3π/2)+sin(x+2π)
  =sin(x)cos(π/2)+cos(x)sin(π/2)+sin(x)cos(π)+cos(x)sin(π)+sin(x)cos(3π/2)
   +cos(x)sin(3π/2)+sin(x)cos(2π)+cos(x)sin(2π)
  =0+cos(x)-sin(x)+0+0-cos(x)+sin(x)+0
  =0




Je ne comprend pas ce que tu fais à l'exercice 3?
j'ai développé , c'est tout.................